CONTRATAÇÃO INTEGRADA NA UNIVERSIDADE FEDERAL DO RIO GRANDE DO SUL - Yamauchi, Vander; Wiese, Ricardo Soccas (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article aims to contribute on the debate about a brazilian public acquisition modality called Contratação Integrada (Integrated Contracting). Where, unlike other existing modalities, the project and the construction are contracted together. In this work, the Integrated Contracting is approached from the perspective of the project process. A comparison between the four cases in which the Integrated Contracting were applied at the Universidade Federal do Rio Grande do Sul (a federal university of Brazil) is presented. The data, obtained from institutional documents, reinforces some questions raised by other authors, such as the importance of the integration between project and construction. It is noted that the Integrated Contracting allows a closer contact between designers and constructors, however, its effectiveness relies on the contractor's ability to coordinate projects and his relationship with the bidder.